The Usage of Subject Category in Cognitive Linguistics (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The concept "money" (or conceptual semantics) is a mental unit that exists in the conceptual sphere of all communicators in the language, and has a universal nature, because it contains all the knowledge related to the conceptual semantics of "money" according to the situation in the perception of an objective existence by verbal and non-verbal means, that is, verbalizers is an important conceptual phenomenon that requires to be realized through communication, and therefore has a uniquely framed (moulded) content from the point of view of communicative need. This article examines linguopragmatic and linguocultural characteristics of verbalizers representing the concept of "money" in English, Uzbek and Russian languages and the author tries to analyze the national and cultural peculiarities of this concept in three languages.